Implikasi Sertifikasi Halal terhadap Perkembangan Industri Halal di Indonesia - Yuningsih M, A. Alfira; Putri, Riska Erfiana; Jubba, Hasse (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2023)
The globalization of halal certification bodies in numerous nations indicates that halal issues are on the rise, which bodes well for the industry's expansion prospects. The purpose of this article is to examine the ramifications of halal certification on Indonesian industries, with a specific focus on the culinary and tourism sectors. By conducting a comprehensive literature review and employing a descriptive qualitative methodology, this research compiled data from pertinent scholarly journals, books, periodicals, and electronic media, including the official websites of the LPPOM-MUI and BPJPH assembly. The results of the study underscore the favorable consequences that halal certification can have on the development of the halal sector and the economy of Indonesia. In addition to providing consumers with information and protection regarding the halal status of products, halal certification serves as a mechanism for conducting business in accordance with Sharia principles. Acquiring halal certification confers a distinct competitive advantage upon businesses, bolstering consumer trust and generating amplified advantages. Moreover, this facilitates the government's efforts to stimulate the Indonesian economy and gain access to the worldwide halal food market. It is established that halal certification increases demand for halal products, thereby solidifying the halal industry's position as a major participant on the international stage. The implication of this research is for business actors and the government that halal certification strengthens the gaining position of a product.